2011
DOI: 10.7551/mitpress/7989.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Democracy's Arsenal

Abstract: An expert explains why the security needs of the twenty-first century require a transformation of the defense industry of the twentieth century. New geopolitical realities—including terrorism, pandemics, rogue nuclear states, resource conflicts, insurgencies, mass migration, economic collapse, and cyber attacks—have created a dramatically different national-security environment for America. Twentieth-century defense strategies, technologies, and industrial practices will not meet the security re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One analysis concluded that of 330,000 US acquisition programmes reviewed only 372 were considered problematic, a statistically insignificant value. 63 Another source concurs that fewer than 0.1 per cent of the 15 million annual acquisition purchases in the US involve some kind of fraud or abuse. 64 The data therefore indicate that the challenges for US defence acquisition are not to be found in incidences of fraud or malpractice.…”
Section: The Regulation and Control Of Defence Businessesmentioning
confidence: 97%
“…One analysis concluded that of 330,000 US acquisition programmes reviewed only 372 were considered problematic, a statistically insignificant value. 63 Another source concurs that fewer than 0.1 per cent of the 15 million annual acquisition purchases in the US involve some kind of fraud or abuse. 64 The data therefore indicate that the challenges for US defence acquisition are not to be found in incidences of fraud or malpractice.…”
Section: The Regulation and Control Of Defence Businessesmentioning
confidence: 97%
“…The post-cold war decrease in defense budgets and procurements were the largest decrease since World War II. 19 Between 1985 and 1995 tank procurement went from 720 systems to 0 systems in 1995. 20 Furthermore, during this same period, defense contractors underwent a significant merger process with the number of major defense contractors dropping from over 50 to 6.…”
Section: Condition Of the Defense Industrial Basementioning
confidence: 99%
“…28 An example of how this process has failed to work took place in 2003 when Boeing included a small export controlled computer chip (an item with dual military and commercial application) on a commercial airline sold to China, and subsequently received a fine of $15 million for violating export controls. 29 This situation demonstrates a dilemma for potential DoD suppliers. If a supplier produces a commercial item that is used in a weapons system, then this item falls under more stringent export control laws, which frequently discourage producers from going into the DoD market.…”
Section: Condition Of the Defense Industrial Basementioning
confidence: 99%
See 1 more Smart Citation